PENGARUH PEMBERIAN KONSELING PADA PASIEN HEMODIALISA DENGAN TINGKAT KEKAMBUHAN PENYAKIT HIPERTENSI DI RUMAH SAKIT KOTA MEDAN - Silaen, Harsudianto (Universitas Prima Indonesia, 2019)
Counseling is one of the effective ways in health education to teach patients to limit their fluid intake. Through counseling the relationship between nurses and patients can be more open, where patients can express all complaints and limitations and / or their abilities and weaknesses, nurses can also explore patient feelings and understand the diversity of each different patient, so that communication between nurses and patients can be adjusted with the diversity of characteristics that patients have. In patients Renal failure is often found as a complication of long-standing hypertension and can interfere with the process of hemodialysis. Therefore sufferers need to be assisted in the form of counseling. This study aims to determine the effect of counseling on hemodialysis patients with recurrence rates of hypertension in Medan City Hospital. This type of research is quantitative with a quasi-experimental design. The sample used in this study amounted to 54 people and the sampling technique with purposive sampling was that sample taking by researchers came to do research and a portion of the sample was taken from the population. Data collection uses questionnaires and data analysis using the T-Test. From the results of the study, the effect of giving counseling with the recurrence rate of hypertension was obtained that the p value was 0.001. It is expected that nurses will provide education and counseling to hemodialysis patients to be able to control diet patterns.